Literature Review: Peluang Dan Tantangan Penggunaan Keceerdasan Buatan Dalam Meningkatkan Pelayanan Farmasi Klinis - farah; Putri Auliya Serawaidi, Nadya (Jurnal Kesehatan Mahardika, 2025)
Artificial Intelligence offers opportunities has to optimize clinical pharmacy services in hospitals or other pharmaceutical services. AI can assist clinical pharmacists in the field of clinical pharmacy such as prescription review, therapeutic drug monitoring, monitoring of drug adverse effects, and providing drug information services. The aim of this literature review is to analyze and summarize the opportunities and challenges of AI in supporting clinical pharmacy services. This study uses a literature review method with a qualitative research approach. The selected journal criteria are journals published between 2015 and 2025 and are fully accessible. From the review, eight journals were found that met the criteria for analysis. The result of this literature review indicate that AI can enhance the quality and effectiveness of clinical pharmacy services. The development of AI in clinical pharmacy has just begun, and there are several challenges that need to be addressed, such as data bias, data security, the lack of regulations and ethics, and resistance to AI usage. Evaluation and collaboration with other healthcare professionals and technology experts are needed to improve AI-based clinical pharmacy services.